Scabies among the French armed forces in 2015. Issue 3 (September 2016) - Brossier, Constance; Morand, Jean-Jacques; Breton, Anne; Gallineau, Cyrille; Thauvin, Xavier; Berger, Franck; Meynard, Jean-Baptiste; Michel, Remy; Duron, Sandrine
Highlights: Incidence of scabies among French armed forces was estimated at 11 cases per 10, 000 person-years in 2015. Scabies is complex to handle notably in community settings. Physicians should be well trained and informed on scabies management to control its spread and limit re-infestation.